Q&A: ICTs and livestock performance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
South Africa´s ARC Animal Improvement Institute (ARC-AII) is working to improve the biological and economic efficiency of animals through scientific research, development, evaluation and technology transfer. Deputy Director Dr Japie van der Westhuiz